Biodiversity and ecology of coastal wetlands in Ghana - Ryan, J.M.; Ntiamoa-Baidu, Y. (Biodiversity and Conservation, 2000)
Coastal wetlands are transition zones between terrestrial marine and aquatic habitats; consequently they exhibit relatively unique habitat and species diversity. Estuaries, deltas, and lagoons are among the most biologically productive but least understood ecosystems in the world. In the recent past, the world’s coastal wetlands have been drained and destroyed by conversion to agricultural land, or by industrial and urban development. Wetlands have often been overlooked or misunderstood, but scientists and coastal managers are learning that these ecosystems provide essential services. Such services include the storage of runoff, denitrification and detoxification of polluted water, prevention of shoreline erosion, and they serve as important breeding and feeding grounds for fish, shellfish, and birds. Ghana’s 550 km of coastline includes over one hundred estuaries and lagoons. These coastal wetlands are on the boundary of two major migration corridors for waterbirds: the East Atlantic Flyway and the Mediterranean Flyway. Studies by the Save the Sea Shore Birds ‐ Project and the Ghana Wildlife Society dating back to the early 1980s, have shown that significant numbers of waterbirds use Ghana coastal wetlands as staging areas and wintering grounds. At least 15 species of waterbirds occur here in internationally important populations (Ntiamoa-Baidu 1991). Five coastal lagoons and their watersheds along the Ghana coast have been proposed as Ramsar sites (internationally important wetlands) under the Convention on Wetlands of International Importance (Ramsar Convention). In 1992, the government of Ghana received support from the Global Environment Facility (GEF) for the protection of these sites (Muni-Pomadze, Densu delta, Sakumo, Songor, and Keta) under the Coastal Wetlands Management Project (CWMP), which is implemented by the Ghana Wildlife Department. The CWMP seeks to preserve the ecological integrity of these five coastal wetlands, and to enhance the socio-economic benefits that these wetlands provide to the local communities (Ntiamoa-Baidu and Gordon 1991; Piersma and Ntiamoa-Baidu 1995). To fulfil the CWMP’s goals, baseline information on the ecological health and integrity of these wetland ecosystems is required before sound management decisions can be made. Toward that end, the CWMP has implemented a series of baseline ecological studies aimed at characterizing the current status of these